Literatura infantil como experiência de formação: um estudo com obras de Ruth Rocha - Carleto, Eliana Aparecida (2014)
This research investigates children‟s literature as an educational experience. Its aim is to analyze the contributions of Ruth Rocha‟s children‟s literature to teacher education and to reader education. Collaborative action-research is the methodology used in this investigation that focuses public primary school education teachers‟ built knowledge and practice. The research methodology consists of: broadband survey questionnaire answered by first years of primary school teachers and school administrators from local public schools of the city of Uberlândia in the state of Minas Gerais in Brazil; documental and bibliographic study; workshops with first years of primary school teachers; participatory observation in the schools, field notes; interviews with subjects about knowledge and educational experiences with children‟s literature books in classroom; transcription and interview report. Actions involving the work with children‟s literature books at school are also part of this project. The subjects involved were one hundred and twenty-five students of first, and second and third years of primary school, and thirteen teachers: three library teachers, two language and literature teachers, one grade-two teachers, two grade-three teachers, three coordinators, one readapted teacher for library teaching work, and an elementary school Portuguese teacher with experience in library collections selection. The research was conducted at two local public schools in Uberlândia. The study emphasized that although the City Centre of Studies and Educational Projects Centro Municipal de Estudos e Projetos Educacionais Julieta Diniz (CEMEPE) offered in-service teacher training sessions they did not offer any specific training in reading children‟s literature with focus on the teacher or on the student reading education. It was also verified that the teachers wished to help their students to become critical readers but, in their everyday practice at school, they used methodologies that did not involve students as active readers as they worked children‟s literature. Their work was a linear repetitive way of teaching where students had to complete reading records and to do mere comprehension exercises of texts and literature books read. Most subjects (60%) did not know about any existing governmental programs to enhance reading skills, such as the national program of library in the school - Programa Nacional Biblioteca da Escola PNBE‟, and they even did not study about children‟s literature. In the schools involved in this research, making use of Ruth Rocha‟s work, we worked some actions along with the subjects building knowledge, attitude changes, and reading practice in the school context.